Patterns of DSM-IV Alcohol Abuse and Dependence Criteria Among Adolescents and Adults: Results From the 2001 National Household Survey on Drug Abuse - Harford, Thomas C.; Grant, Bridget F.; Yi, Hsiao-ye; Chen, Chiung M. (Alcoholism, clinical and experimental research, 2005)
Background: Studies of the prevalence of DSM‐IV alcohol use disorders (AUDs) in general population samples of adolescents and adults are rare. Comparisons of the prevalence of alcohol abuse and dependence in adolescent surveys with the prevalence in adult general population surveys are confounded by differences in survey design and measurement, thereby reducing their validity. The purpose of the present study was to examine the effects of age, sex, race/ethnicity, and drinking status on the prevalence of DSM‐IV alcohol abuse and dependence (including diagnostic orphans) and associated diagnostic criteria among adolescents and adults aged 12‐65 years in a single representative sample of the US population. Methods: This study was based on data from the 2001 National Household Survey on Drug Abuse public use file. Of the 55,561 subjects in the survey, 33,576 (60.5%) reported alcohol use in the past year and provided information on DSM‐IV AUD criteria. DSM‐IV AUD criteria were assessed by questions related to specific symptoms occurring during the past 12 months. Results: Overall, the most prevalent criteria of DSM‐IV alcohol dependence were “tolerance” and “time spent obtaining alcohol, drinking, or getting over its effects.” The most prevalent criterion of DSM‐IV alcohol abuse was “hazardous use.” The prevalence of alcohol abuse only and of dependence with and without abuse was highest among respondents aged 18‐23 years, followed by respondents aged 12‐17 years, and lowest among respondents aged 50 years and older. Among subgroups of current and heavier drinkers, differences between adolescents and young adults were less pronounced, especially among females. For each age group, the prevalence of alcohol abuse only was greater than the prevalence of dependence (with or without abuse). The abuse‐to‐dependence ratios also were generally consistent across age groups and slightly higher among males (2.1:1.0) than females (1.6:1.0). Conclusions: The higher prevalence for some dependence criteria among adolescents and young adults as measured in the present study may blur the distinction between symptom reports associated with the normative development of drinking patterns and clinically relevant aspects of DSM‐IV alcohol dependence.